2007
DOI: 10.1089/jmf.2006.271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Bicarbonate and Albumin on theIn VitroWater-Holding Capacity and Some Physiological Properties ofTrigonella foenum graecumL. Galactomannan in Rats

Abstract: This study seeks to improve the beneficial effects of fenugreek (Trigonella foenum graecum L.) galactomannan (GM) in lowering the plasma lipid profile and weight. Three different combinations of diets were prepared with fenugreek GM--(a) fenugreek GM + water (GM); (b) fenugreek GM + sodium bicarbonate (GMB); and (c) fenugreek GM + bicarbonate + albumin (GMBA)--and their in vitro water retention capacity and in vivo lipid-lowering effect were studied. Distilled water and sodium bicarbonate were used as controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The physiological effects of fenugreek seeds can be attributed to its fiber and high saponin content 166 . Fenugreek has been previously reported to significantly reduce fasting blood sugar and improve glucose tolerance, 167 , 168 reduce oxidative stress, 169 , 170 improve the lipid profile, and reduce body weight 171 in animal models. It has also shown immunomodulatory effects in animal models 172 .…”
Section: Dietary Fibermentioning
confidence: 99%
“…The physiological effects of fenugreek seeds can be attributed to its fiber and high saponin content 166 . Fenugreek has been previously reported to significantly reduce fasting blood sugar and improve glucose tolerance, 167 , 168 reduce oxidative stress, 169 , 170 improve the lipid profile, and reduce body weight 171 in animal models. It has also shown immunomodulatory effects in animal models 172 .…”
Section: Dietary Fibermentioning
confidence: 99%
“…HFS-fed rats tended to lose body weight significantly when treated with nut mucilage of Calophyllum inophyllum at doses of 250 and 500 mg/kg (Figure 2a). Such observation is an illustration of the weight-loss properties commonly attributed to soluble dietary fibers like mucilages and gums (Dakam et al, 2007;Boban et al, 2006;Enzi et al, 1980). It is recognized that the weight-loss properties of soluble fibers are closely linked to the viscosity when they are in contact with water molecules in the gut (Papathanasopoulos & Camilleri, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Fenugreek galactomannan was used as reference soluble dietary fiber and was administered to a group of HFS-fed rats (HFS-Fg500). Treatment doses (250 and 500 mg/kg) were determined according to a previous study of metabolic effects of fenugreek galactomannan in rodents (Dakam et al, 2007). The experimental scheme is summarized below: SD-Ctrl: standard laboratory diet + distilled water HFS-Ctrl: high-fat/high-sucrose diet + distilled water HFS-Sat: standard laboratory diet + distilled water HFS-Ci250: high-fat/high-sucrose diet + C. inophyllum nut mucilage at 250 mg/kg HFS-Ci500: high-fat/high-sucrose diet + C. inophyllum nut mucilage at 500 mg/kg HFS-Fg500: high-fat/high-sucrose + fenugreek galactomannan at 500 mg/kg Distilled water, nut mucilage, and fenugreek galactomannan were administered to rats by a single daily oral gavage over 14 days.…”
Section: Phase 2: Study Of Metabolic Effects Of C Inophyllum Mucilagementioning
confidence: 99%
See 1 more Smart Citation
“…Animal trials on fenugreek have shown impressive results for health issues connected with weight gain and obesity, including improvements in fasting blood glucose, glucose tolerance, oxidative stress, and lipid profiles 11 14 . Some of these effects have been replicated in humans, and fenugreek has been definitively shown to reduce fasting blood sugar and improve glucose tolerance in people with type 1 diabetes and to enhance lipid profiles, insulin sensitivity, and glucose control in folks with type 2 diabetes 15 , 16 .…”
Section: Fenugreekmentioning
confidence: 99%